Self-reported oral health status and self-care practices among mid-life women at a secondary care hospital in a rural area of Delhi, India - Saurav Basu; Ruchira Pangtey; Bratati Banerjee; Saurabh Kumar (Shahid Beheshti University of Medical Sciences, 2021)
Background: Poor oral health status is more likely among socioeconomically disadvantaged women and low literacy due to poor oral hygiene. Onset of menopausal symptoms also triggers hormonal changes, adversely influencing oral health. The study objective was to determine the self-reported oral health status and self-care practices among perimenopausal women attendees of the medical outpatient department of a government hospital in Delhi, India  Methods: We conducted a cross-sectional study at a secondary care hospital among 136 women aged 40-59 years, having either perimenopause symptoms or with menopause. Data were collected through face-to-face interviews using the Hindi version of the WHO Steps Module on Oral Health. A p-value < 0.05 was considered statistically significant. Results: Sixty-nine (51.2%) participants had not received any schooling. Oral health status was reported as average or poor by 61 (44.85%) and 59 (43.4) participants for their teeth and gums, respectively. Pain or discomfort in teeth was reported by 77 (56.6%) participants, along with chewing 66 (48.5%) and speech difficulties 21 (15.4%). Most participants 114 (83.8%) brushed their teeth only once a day, and rarely (3.7%) flossed.  Participants with low education and a greater number of missing teeth were significantly more likely to report suboptimal dental health status. Conclusion: A large proportion of mid-life socioeconomically vulnerable women in India report poor oral health and hygiene with self-perceived suboptimal teeth or gum status. Visually oriented information, education, and communication (IEC) campaigns for oral health promotion should be evaluated in public health facilities.